The Concept of Monopoly and the Measurement of Monopoly Power - Lerner, A. P. (Review of Economic Studies, 1934)
Journal Article The Concept of Monopoly and the Measurement of Monopoly Power Get access A. P. Lerner A. P. Lerner London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 3, June 1934, Pages 157–175, https://doi.org/10.2307/2967480 Published: 01 June 1934